Food-leftover sharing intentions of consumers: An extension of the theory of planned behavior. (July 2023) - Kirmani, Mohd Danish; Fatah Uddin, S.M.; Sadiq, Muhammad Ahsan; Ahmad, Asad; Haque, Md Asadul
Abstract: The study is grounded on the premise that the food-leftover sharing practice can simultaneously contribute to resolving the problems of food shortage and food wastage. The primary aim of the study was to identify the factors influencing consumer intentions to share food leftovers. The study was conducted in four stages. First, a comprehensive literature analysis was done to identify the relevant factors and underlying relationships among them. Second, a research instrument was designed, and pretesting was conducted to check the appropriateness of the research instrument with the study context. Third, a pilot study was performed on the 194 respondents to check the dimensionality of the study scales. Four, the final data was collected and analyzed from a sample of 331 (collected through offline and online modes) using structural equation modeling in AMOS 24. The pilot and final study data were collected from New Delhi (An Indian metropolitan city). The study findings suggest that the TPB constructs i.e. subjective norms, attitude, and perceived behavior control influence consumer intentions to share food leftovers. Additionally, religiosity, moral obligation, and environmental concern were observed to be the predictors of attitude toward the practice of food-leftover sharing. This study offers food leftover sharing as a solution to food waste generation and hence, aligned with the sustainable development goals (SDG -12) i.e., responsible consumption and production. Highlights: Theory of Planned Behaviour constructs influence consumer intentions to share food leftovers. Religiosity influences consumer attitude towards food-leftover sharing. Moral obligation influences consumer attitude towards food-leftover sharing. Environmental concern influences consumer attitude towards food-leftover sharing.